Transformational and transactional sales leadership during a global pandemic. Issue 4 (7th December 2022) - Alavi, Sascha; Ehlig, Pia Anna; Habel, Johannes
Abstract: Transformational (TFL) and transactional leadership (TAL) are foundational leadership styles in sales practice and have been intensively studied by past sales research. However, prior research conflicts on the effectiveness of TFL and TAL to help salespeople cope with the persisting changes of a global pandemic, such as COVID-19. Combining leadership theory with perceived uncertainty theory, we develop and test a longitudinal growth model explaining how TAL and TFL affect sales performance during the emerging COVID-19 pandemic. Using transactional and survey data of 16, 275 customers and their respective salespeople during the first months of the pandemic, we show that sales performance declined and that TAL was more effective than TFL at mitigating the drop of sales performance. We ascribe this finding to salespeople's uncertainty resulting from the persisting changes brought about by the pandemic, which requires leaders' continuous feedback rather than a focus on long-term visions. To substantiate our findings, we conducted a second study confirming that an increase in TAL is more effective at mitigating the performance decline and that salespeople's perceived effect uncertainty and response uncertainty moderate this effect. Our findings offer timely and valuable implications for leadership theory and practice how to manage pandemic challenges.